Breakaway [compact disc, unabridged] - Hirsch, Jeff (39 clues. Unstoppable, 2013)
Dan and Amy are facing their greatest threat yet: an enemy who has found a way to use the source of the Cahill family power against them. To stop him, Dan and Amy must set out on a desperate mission that will take them from one of the world's hottest regions all the way to the frozen blast of the Arctic Circle. But with the enemy closing in, Dan finds himself facing the one terror he never imagined: being betrayed by his own sister.